Association between the CYP2B6 polymorphisms and nonnucleoside reverse transcriptase inhibitors drug-induced liver injury: a systematic review and meta-analysis - Noppadol Chanhom; Janjira Sonjan; Jarupat Inchai; Wanvisa Udomsinprasert; Usa Chaikledkaew; Supharat Suvichapanich; Surakameth Mahasirimongkol; Jiraphun Jittikoon (Scientific Reports)
Abstract Nevirapine (NVP) and Efavirenz (EFV) can cause antiretroviral drug-induced liver injury (ARVDILI). The objectives of this study were to summarize and analyze existing data on pharmacogenomics associated with nonnucleoside reverse transcriptase inhibitors drug-induced liver injury using systematic review and meta-analysis. This study systematically searched the relevant studies regarding pharmacogenes related to ARVDILI from online databases. Genes-encoding proteins were further analyzed using the STRING program to determine the protein-protein interactions (PPI). CYP2B6 polymorphisms were further meta-analyzed. Seventeen genes have been shown to be significantly associated with ARVDILI. Illustration from STRING analysis, CYP2B6, CYP1A1, and CYP2D6 enzymes have been recognized as central proteins linked to all other analyzed proteins. Meta-analysis illustrated that CYP2B6 *1/*6 (OR = 1.83; 95% CI: 1.15–2.90; P = 0.01), *6/*6 (OR = 2.48; 95% CI: 1.28–4.79; P = 0.007), and *1/*6 plus *6/*6 (OR = 1.94; 95% CI: 1.24–3.01; P = 0.003) were associated with risks of EFV-induced liver injury. Moreover, CYP2B6 *1/*6 (OR = 0.44; 95% CI: 0.22–0.91; P = 0.03) and a group combining individuals with either *1/*6 or *6/*6 (OR = 0.42; 95% CI: 0.21–0.84; P = 0.01) were associated with reduced risks of NVP-induced liver injury. This meta-analysis revealed an association between CYP2B6 genetic polymorphism and susceptibility to ARVDILI.